Towards Lasing Without Inversion in Neutral Mercury. (18th March 2015) - Rein, Benjamin; Sturm, Martin R; Walser, Reinhold; Walther, Thomas
Abstract: Currently, we are implementing a lasing without inversion (LWI) scheme in mercury based on calculations by Fry et al. [1]. A recent detailed analysis predicting exact experimental parameters shows the feasibility of our LWI scheme [2]. In this paper we report on the progress of our experiment and compare its parameters with the prior analysis.